If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3x + -5y + 3) = 0 Reorder the terms: -1(3 + 3x + -5y) = 0 (3 * -1 + 3x * -1 + -5y * -1) = 0 (-3 + -3x + 5y) = 0 Solving -3 + -3x + 5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + -3x + 3 + 5y = 0 + 3 Reorder the terms: -3 + 3 + -3x + 5y = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -3x + 5y = 0 + 3 -3x + 5y = 0 + 3 Combine like terms: 0 + 3 = 3 -3x + 5y = 3 Add '-5y' to each side of the equation. -3x + 5y + -5y = 3 + -5y Combine like terms: 5y + -5y = 0 -3x + 0 = 3 + -5y -3x = 3 + -5y Divide each side by '-3'. x = -1 + 1.666666667y Simplifying x = -1 + 1.666666667y
| 2.00+35*.30=x | | 9y^2-169x^2= | | 4=w-6 | | f(x)=3x-20 | | 5c^3+20c^2-105c=0 | | -3x-y=9 | | 8y+17=3y-3 | | 4x-3(x-1)=9x+15-7x | | 2r^2+r-15=0 | | (0.4x)-(2x)-(.8)=1.4 | | 9(d+8)= | | 2(3x+2)=6x+5 | | f(x)=4x-8 | | 5(d-5)+6= | | n=0.08*7496+7400 | | 6x+9y=15 | | 2(3x+2)=6x+2 | | 2.00+x*.30=12.50 | | 14=2+x | | 2(x-5)+7=8x | | 2b-6-11b-5= | | -3(t-2)+6t=7t-4 | | (5-6m)/m^2-9 | | 9(x+5)=8(x-6)+x | | f(16)=4x-8 | | 4(X+7)=2 | | 14a+16a= | | 9(x-5)=8(x-6)-x | | n^2-2-12=0 | | 5(2+x)+3x=-2(x+5) | | -3(-x+2)=2x-4 | | 176r=16 |